Impact of the fliF Gene on Biotite Weathering of Rhizobium pusense S41. Issue 4 (20th April 2020) - Wang, Yuanli; Li, Lei; Sun, Yue; He, Linyan; Sheng, Xiafang
Abstract: Rhizobia have been reported to weather silicate mineral, however, molecular mechanisms underlying mineral weathering of Rhizobium strain is unclear. In this study, biotite weathering behaviors were compared among the mineral-weathering Rhizobium pusense S41, its mutants created by deleting the fliF gene involved in flagellar protein synthesis, and its complemented strain. Flagellum was observed in strain S41 but not in its mutant S41Δ fliF . Mobilized Fe and Al concentrations decreased in the presence of S41Δ fliF during mineral weathering process compared to strain S41. No significant differences in the gluconic acid concentration and pH values were found between strains S41 and S41Δ fliF during the mineral weathering process except for day 2. A similar bacterial growth in the culture medium was observed between strains S41 and S41Δ fliF, however, significantly lower cell numbers on the mineral surface were observed for S41Δ fliF compared to strain S41. Furthermore, biofilm production was depressed for S41Δ fliF compared to strain S41. The results showed the important role of a flagellum of strain S41 in biotite weathering and that the fliF gene of strain S41 exhibited important impacts on mineral weathering activity and biofilm production.